2003
DOI: 10.1038/sj.ijo.0802400
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking is associated with energy balance in premenopausal African-American adult women differently than in similarly aged white women

Abstract: OBJECTIVE:To investigate the differential association of cigarette smoking with energy balance in African-American and white premenopausal women. DESIGN: Cross-sectional study of energy balance, weight, and smoking in women. SUBJECT: A total of 374 women: 191 African-American (mean age ¼ 29.876.5 y) and 183 white women (mean age ¼ 28.977.1 y). MEASUREMENTS: Weight, cigarette smoking habits, resting energy expenditure, dietary intake, and physical activity. RESULTS: There were no significant differences in diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Specifically, amongst black women, heavy smoking was associated with 218 kcal/d higher REE and moderate smoking with 177 kcal/d higher REE compared to non-smokers. Although studies on the effect of smoking in diabetic nephropathy or those with CKD have not been reported, the results of this study are in line with those reported by others in populations without CKD [ 16 , 37 ] and extend these observations to patients with CKD. Exactly how chronic smoking leads to increased REE is not clear from present investigations [ 38 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Specifically, amongst black women, heavy smoking was associated with 218 kcal/d higher REE and moderate smoking with 177 kcal/d higher REE compared to non-smokers. Although studies on the effect of smoking in diabetic nephropathy or those with CKD have not been reported, the results of this study are in line with those reported by others in populations without CKD [ 16 , 37 ] and extend these observations to patients with CKD. Exactly how chronic smoking leads to increased REE is not clear from present investigations [ 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…The magnitude of the effect of smoking was 68 kcal/d which was approximately one-third of the effect size reported in the present study [ 16 ]. In another study, black women who smoked were found to have a greater baseline REE compared to white women [ 37 ]. Specifically, amongst black women, heavy smoking was associated with 218 kcal/d higher REE and moderate smoking with 177 kcal/d higher REE compared to non-smokers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weight gain after smoking cessation is largely because of increased body fat1216. Mechanisms that have been investigated include increased energy intake, decreased resting metabolic rate, and decreased physical activity8,14,19,23,51,52. Studies have not consistently shown increased caloric intake as an explanation for the weight gain following smoking cessation18,53.…”
Section: Discussionmentioning
confidence: 99%
“…Among females, AAW are known to be different than non-AAW in several demographic, psychosocial, and physiological characteristics (Ahmed, Brown, Gary, & Saadatmand, 1994; Andrews, Felton, Ellen Wewers, Waller, & Tingen, 2007; Clemens, Klesges, Slawson, & Bush, 2003; Collins, et al, 2004; Delva, et al, 2006; Ensminger, Smith, Juon, Pearson, & Robertson, 2009; Harrell & Gore, 1998; King, et al, 2006; Manson, Sammel, Freeman, & Grisso, 2001; Rosenberg, Palmer, Rao, & Adams-Campbell, 2002; Sartor, et al, 2009; Wolff, Britton, & Wilson, 2003). Similarly, within the African American population, psychosocial and physiological factors differ between women and their male counterparts (Artinian, Washington, Flack, Hockman, & Jen, 2006; Fox, et al, 2004; King, et al, 1999; Lockery & Stanford, 1996; Murtaugh, Borde-Perry, Campbell, Gidding, & Falkner, 2002; Nollen, Catley, Davies, Hall, & Ahluwalia, 2005; Pulvers, et al, 2004; Qureshi, Suri, Zhou, & Divani, 2006; Savoca, et al, 2009; Woods, Harris, Ahluwalia, Schmelzle, & Mayo, 2001).…”
Section: Introductionmentioning
confidence: 99%